The Effect of Democratic Leadership Style on Employee Performance (Study Cases at the Dompu Education and Culture Office Branch Office) - Syamsuddin, Syamsuddin (STKIP Yapis Dompu, 2023)
Research is Mix Method research which is a combination of qualitative and quantitative research methods. Quantitative research can be interpreted as a method study which grounded on philosophy positivism, used for researching on population or certain samples, technique taking sample is generally done randomly, data collection using research instrument, data analysis is quantitative/statistical with the aim to test the hypotheses that have been implemented in his book. While the use of qualitative research methods is a data collection technique that is carried out by using the method of observation, interviews and documentation, then the data obtained is analyzed using data reduction, data presentation, and drawing conclusions. After that the data was tested with the validity of the data using source triangulation. The analysis of the data is quantitative/statistical in nature with the aim of testing the hypotheses that have been applied in the book. The results of hypothesis testing on the democratic leadership variable were carried out by the Head of the Dompu Education and Culture Office Branch Office at a sig. 0.0 0 <0.05 on the t test and sig. 0.015 <0.05 on the F test and a value of Fgitung 5.258 > 4.30, so there is a significant influence of democratic leadership variables on employee performance variables. This means that the higher the democratic leadership style, the higher the performance of employees at the Dompu Education and Culture Office Branch Office, so between both of them there is correlation.